2016
DOI: 10.1161/circimaging.116.005032
|View full text |Cite
|
Sign up to set email alerts
|

Association of Impaired Glucose Regulation and Insulin Resistance With Cardiac Structure and Function

Abstract: Background We examined the relationship between glucose homeostasis and comprehensive measures of cardiac structure and function among a representative sample of U.S. Hispanics. Methods and Results ECHO-SOL, an echocardiographic ancillary study of The Hispanic Community Health Study/Study of Latinos (HCHS/SOL), enrolled 1,818 Hispanic/Latino men (43%) and women (57%) age≥45 years (mean=56). Glucose intolerance was defined as: i) Prediabetes: HbA1c≥5.7 and <6.5%; ii) Diabetes: fasting plasma glucose≥126 mg/dL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…Previous cross‐sectional large‐scale community‐based studies have demonstrated an independent association of subclinical LV remodeling and dysfunction with insulin resistance 10, 11, 12, 13, 14, 15. On the other hand, population data on the longitudinal changes of LV structure and function in relation to insulin resistance are sparse.…”
mentioning
confidence: 99%
“…Previous cross‐sectional large‐scale community‐based studies have demonstrated an independent association of subclinical LV remodeling and dysfunction with insulin resistance 10, 11, 12, 13, 14, 15. On the other hand, population data on the longitudinal changes of LV structure and function in relation to insulin resistance are sparse.…”
mentioning
confidence: 99%
“…Duration of diabetes, age and abnormally elevated levels of Hb1AC were independently correlated with LVDD in several studies (15,21,27,28,29). An independent relationship between LVDD and BMI was also reported (18,22,28). Other studies found no independent correlation between alteration of diastolic function and poor glycemic control (19,23).…”
Section: Epidemiologic and Clinical Aspectsmentioning
confidence: 92%
“…Holzman et al reported a continuous relationship between values of fasting plasma glucose and HbA1C and LVDD in a middleaged non-diabetic population, suggesting early development of LV alterations even in prediabetic states (17). In a large study, which investigated the relationship between glucose homeostasis and LV structure and systolic/diastolic function, glucose intolerance and insulin resistance were associated with measures of diastolic dysfunction even in stages preceding the development of DM (18). In newly diagnosed (within 1 month) normotensive type 2 DM subjects aged between 30-60 years, LVDD was present in 41% of patients.…”
Section: Epidemiologic and Clinical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Claudia Mendoza-Pinto, 1 Pamela Munguía-Realpozo, 2 Liliana Aquino, 1 Adalberto Ramírez-Hernández, 2 Roberto Berra-Romani, 1 Aurelio López-Colombo, 1 Mario García-Carrasco. Background/Purpose Insulin resistance (IR), which adversely impacts left ventricular (LV) remodeling and function in middle-aged patients.…”
Section: Assessment Of Left Ventricular Using Speckle Tracking Echocamentioning
confidence: 99%